Pendekatan Holistik Dalam Pencegahan Hipertensi, ISPA dan Hidup Sehat Di Masyarakat (Edukasi dan Skrining) - Indriani, Cece; Ardiansyah, La Ode; Solihin, Solihin; Saparina, Titi; Hasanuddin, Silviana (Journal of Health Innovation and Community Services, 2025)
Hypertension and acute respiratory infections (ARI) are two major public health issues in Indonesia. Hypertension is often called the “silent killer,” with a prevalence of up to 34.1% among the adult population. Meanwhile, the high incidence of ARI in communities driven particularly by air pollution and open-waste burning poses a significant challenge.This community service initiative aims to enhance public knowledge and awareness of healthy lifestyles to prevent hypertension, as well as environmental management and respiratory hygiene to reduce the risk of ARI. The project was carried out by thematic community service students (KKN Tematik) in Rapambinopaka Village, Lalonggasumeeto District, under the supervision of multidisciplinary faculty advisors in nursing, public health, environmental sanitation, and pharmacy. Methods included interactive health education, blood pressure screening, healthy lifestyle demonstrations, and advocacy on waste management to prevent air pollution that triggers ARI. Implementation was structured around lectures, Q&A sessions, poster distribution, and both pre‑test and post‑tests to assess changes in participants’ understanding. Results showed a significant increase in knowledge. In terms of hypertension, participants demonstrated a positive shift in awareness regarding routine blood pressure monitoring and adapting a low‑salt diet. Meanwhile, in the ARI intervention component, community members improved their ability to sort waste and avoid burning, aligning with an effective environmental management model. Conclusion is the integrated intervention combining health education and environmental management successfully enhanced preventive attitudes and behaviors toward hypertension and ARI. A key recommendation is the continued involvement of local health cadres and integration with Puskesmas or Posyandu facilities to ensure sustainability and expand impact.